The Effect of Remnant Tissue Preservation in Anatomic Double-Bundle ACL Reconstruction on Knee Stability and Graft Maturation - Takahashi, Tsuneari; Kimura, Masashi; Hagiwara, Keiichi; Ohsawa, Takashi; Takeshita, Katsushi (The Journal of Knee Surgery, 2019)
Several investigators have developed anterior cruciate ligament reconstructions (ACLR) with remnant tissue preservation (RTP) and have reported better clinical outcomes. However, the effects of RTP remain controversial. To date, no reports have compared both clinical and radiological outcomes of anatomic double-bundle ACLR using the hamstring tendon and outside-in technique with/without RTP. This article evaluates the effectiveness of RTP in ACLR on knee stability and graft maturation. In total, 75 patients with unilateral ACL injury who had undergone anatomic double-bundle ACLR using autografted hamstring tendon either with RTP (Group P, n = 43) or without (Group N, n = 32) were enrolled. Clinical scores, pre- and postoperative side-to-side differences (SSDs) obtained using Telos, radiological evaluations of the grafted tendon using the signal/noise quotient (SNQ) measured using magnetic resonance imaging, and arthroscopic evaluations of the grafted tendon were retrospectively compared between the groups. Postoperative SSDs were smaller in the Group P (0.78 ± 1.90 mm) than in the Group N (1.29 ± 2.18 mm); however, this difference was not significant. Comparing two subgroups of the Group P, the SSD was significantly smaller in those with sufficient remnant coverage (−0.56 ± 1.38 mm) than in those without (1.48 ± 1.77 mm) (p = 0.019), as well as in the Group N patients (p = 0.019). The degree of synovial coverage of the anteromedial (p = 0.0064) and posterolateral (p = 0.032) bundle grafted tendon at the time of second-look arthroscopy was significantly better in the Group P than in the Group N. SNQ values of ACL grafted tendon at proximal (p = 0.049), middle, and distal (p = 0.039) one-third in Group P were better than those in Group N. RTP may enhance synovial coverage and maturation of the grafted tendon. Sufficient remnant tissue coverage may contribute to better knee stability. This is a Level III, retrospective comparative study.
Keywords: anterior cruciate ligament reconstruction; remnant tissue; Telos; magnetic resonance imaging; arthroscopy